2015
DOI: 10.2140/agt.2015.15.903
|View full text |Cite
|
Sign up to set email alerts
|

Minimally intersecting filling pairs on surfaces

Abstract: Let $S_{g}$ denote the closed orientable surface of genus $g$. We construct exponentially many mapping class group orbits of pairs of simple closed curves which fill $S_{g}$ and intersect minimally, by showing that such orbits are in correspondence with the solutions of a certain permutation equation in the symmetric group. Next, we demonstrate that minimally intersecting filling pairs are combinatorially optimal, in the sense that there are many simple closed curves intersecting the pair exactly once. We conc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 14 publications
1
43
0
Order By: Relevance
“…For a fixed surface S g,p , we will let i g,p denote the minimal geometric intersection number of a filling pair on that surface. As discussed above, the values of i g,p were determined in almost all cases in the works of Aougab-Huang [1] and Aougab-Taylor [2]. However, in the case of S 2,p , p ≥ 3 odd, they showed only the bounds:…”
Section: Preliminariesmentioning
confidence: 99%
“…For a fixed surface S g,p , we will let i g,p denote the minimal geometric intersection number of a filling pair on that surface. As discussed above, the values of i g,p were determined in almost all cases in the works of Aougab-Huang [1] and Aougab-Taylor [2]. However, in the case of S 2,p , p ≥ 3 odd, they showed only the bounds:…”
Section: Preliminariesmentioning
confidence: 99%
“…For (1), [2] produce pairs of filling curves on a closed surface of genus g 3 that intersect 2g − 1 times by an explicit construction. For (2), first note that when p = 0 any pair of curves that fills and intersects 2g − 1 times must have a single disk as its complementary region.…”
Section: Minimal Intersecting Filling Curvesmentioning
confidence: 99%
“…Therefore, to finish the proof of (2) it suffices to exhibit a filling pair on S g,0 , g > 2, intersecting 2g times. Consider the polygonal decomposition of S 2,0 shown in Figure 2, originally constructed in [2].…”
Section: Minimal Intersecting Filling Curvesmentioning
confidence: 99%
“…The combinatorial complexity of a filling X of F g (g ≥ 2), denoted by T k (X), is the number of simple closed curves which intersect the union of curves in X no more than k times. In [4] (Theorem 1.2), Aougab and Huang have proved that T 1 (α, β) ≤ 4g − 2 and equality holds if and only if (α, β) is a minimal filling pair of F g . Fillings of surfaces are well studied in topology and geometry.…”
Section: Introductionmentioning
confidence: 99%
“…It follows from the Euler's equation that if (α, β) is a minimal filling of F g , then i(α, β) = 2g − 1. In [4] (see Theorem 1.1), the authors have shown that for all g = 2, there exist minimal filling pairs of F g and for g = 2, if (α, β) is a filling pair of F 2 , then i(α, β) ≥ 4 (see Theorem 2.17 in [4]). Therefore, there is no minimal filling pair of F 2 .…”
Section: Introductionmentioning
confidence: 99%